Bioprotective effects of different Plant Extracts and Essential Oils against Rhizopus stolonifer and Aspergillus niger causing Post Harvest decay in Grapes - Shamsullah, Syed; Ibrahim, Muhammad; Kakar, Sami Ullah; Nazir, Kiaenat; Jabran, Muhammad; Ahmad, Nabeel; Ahmed, Nasser; Abbas, Amjad (Integrative Plant Biotechnology, 2023)
The grapes (Vitis vinifera) are one of the largely consumed fruits in the world. Grape production in Pakistan has increased in the recent years. These are mainly consumed fresh or as dried raisins. Grapes are highly perishable, which makes them liable to rot during transport, storage, and marketing. The perishable nature of grapes leads to a considerable amount of post-harvest loss. The production and quality of grapes are adversely affected by several abiotic and biotic factors. Two different cities Pishin (Balochistan) and Faisalabad (Punjab) fruit market and stores were selected to collect rotten grapes. The fungal pathogens isolated were identified as A. niger and R. stolonifers. The pathogenicity of isolated pathogens was assessed at different temperatures (5, 20, and 30 °C) on the Thompson seedless grape variety. Infection and proliferation of fungi were found conducive at 30°C. As antifungal agents, three organic origin oils, neem, cinnamon, and clove oils with levels i.e., 500, 1000, 2000 ppm as well as marigold and neem extracts with diverse concentrations of like 12.5, 25, and 50% were employed. Among these organic compounds, cinnamon and clove oils at 2000 ppm exhibited 6.54% and 15.3% decay against A. niger, respectively. Meanwhile, against R. stolonifer, cinnamon and clove oils at 2000 ppm exhibited 12.22% and 6.74% decay, respectively. This study’s findings focus on the effectiveness of both essential oils and plant extract in significantly delaying the decay process caused by fungal pathogens. The present study underscores the protective ability of the plant extracts and natural oils which could be a way forward for eco-safe management of post-harvest diseases of grapes before they reach the market.